Auditing - Howard, Leslie R. (Leslie Reginald) (London : Pitman, 1992)
Includes the most recent statements of accounting practice and auditing guidelines as well as the companies act 1989; focuses on the role of auditors and the requirements which govern their work and covers developments in third party liability, computer auding and statistical auditing.
Includes index.
oif 17/03/15
Loan
Keywords: Auditing